Advances in Construction Materials and Sustainable Environment Select Proceedings of ICCME 2020 - Gupta, Ashok Kumar; Shukla, Sanjay Kumar; Azamathulla, Hazi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises select papers presented at the International Conference on Construction Materials and Environment (ICCME 2020). The topics discussed revolve around the identification and utilization of novel construction materials primarily in the areas of structural engineering, geotechnical engineering, transportation engineering, and environmental engineering. The volume presents a compilation of thoroughly studied and utilized sustainable construction materials in different areas of civil engineering. Newly developed testing methodologies, physical modelling methods, numerical studies, and other latest techniques discussed in this book can prove to be useful for researchers and practitioners across the globe. .
Use of Biochar for Sustainable Environmental Remediation -- Macro-and Micro-Scale Engineering Response of Rigid-Soft Gra-vel-Rubber Inclusions: Insights from Detailed Laboratory and DEM Numerical Investigations -- Structural Health Monitoring of Heritage Structures Using Geotechnical Instruments -- Zinc Based Anodes for Cathodic Protection of Reinforced Concrete Structures -- An Overview: Supplementary Cementitious Materials -- Application of Fe-Tio2 Hybrid Technology (Photo-Fenton and Pho-tocatalysis) in Fixed-Mode for Degradation and Decolorization of RB5 Dye -- Study on Concrete Developed with Recycled Fine Aggregate -- Examination of Platooning Variables on Two-Lane Highways hav-ing Mixed Traffic Situation. .
Keywords: Buildings -- Design and construction; Building materials; Engineering geology; Environmental sciences -- Social aspects; Industrial engineering; Production engineering; Building Construction and Design; Building Materials; Geoengineering; Environmental Social Sciences; Industrial and Production Engineering; Building materials -- Congresses; Building materials -- Environmental aspects -- Congresses; Sustainable construction -- Congresses